Association between quantitative sensory testing and pain or disability in paediatric chronic pain: protocol for a systematic review and meta-analysis. Issue 10 (7th October 2019) - Schoth, Daniel Eric; Blankenburg, Markus; Wager, Julia; Broadbent, Philippa; Zhang, Jin; Zernikow, Boris; Liossi, Christina
Abstract : Introduction: This protocol describes the objective and methods of a systematic review of the association between quantitative sensory testing (QST) measures and pain intensity or disability in paediatric chronic pain (PCP). The review will also assess whether the relationship strength is moderated by variables related to the QST method and pain condition; the use of QST in PCP (modalities, outcome measures and anatomical test sites as well as differentiating between pain mechanisms (eg, neuropathic vs nociceptive) and in selecting analgesics); the reliability of QST across the paediatric age range; the ability of QST to differentiate patients with chronic pain from healthy controls; and differences between anatomical test sites. Methods and analysis: Medline, PsycINFO, CINHAL, Web of Science, Scopus, Cochrane Library and OpenGrey will be searched. English language studies will be eligible if they recruit a sample aged 6–24 (inclusive) with chronic pain, including primary and secondary pain; apply at least one of the following QST modalities: chemical, electrical, mechanical (subgroups include pressure, punctate/brush and vibratory) or thermal stimulus to measure perception of noxious or innocuous stimuli applied to skin, muscle or joint; use a testing protocol to control for stimulus properties: modality, anatomical site, intensity, duration and sequence. Following title and abstract screening, the full texts of relevant records will be independently assessed by two reviewers. For eligible studies, one reviewer will extract study characteristics and data, and another will check for accuracy. Both will undertake independent quality assessments using the Appraisal Tool for Cross-Sectional Studies. A qualitative synthesis will be presented with discussion centred around different QST modalities. Where eligible data permit, meta-analyses will be performed separately for different QST modalities using comprehensive meta-analysis. Ethics and dissemination: Review findings will be reported in a peer-reviewed journal and presented at conferences. The study raises no ethical issues. PROSPERO registration number: CRD42019134069.